1998
DOI: 10.1002/(sici)1097-4636(19980615)40:4<577::aid-jbm9>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of calcification of glutaraldehyde-crosslinked porcine aortic cusps by ethanol preincubation: Mechanistic studies of protein structure and water-biomaterial relationships

Abstract: Clinical usage of bioprosthetic heart valves (BPHVs) fabricated from glutaraldehyde-pretreated porcine aortic valves is restricted due to calcification-related failure. We previously reported a highly efficacious ethanol pretreatment of BPHVs for the prevention of cuspal calcification. The aim of the present study is to extend our understanding of the material changes brought about by ethanol and the relationship of these material effects to the ethanol pretreatment anticalcification mechanism. Glutaraldehyde-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…For instance, ethanol preincubation is known to be effective in preventing the calcification of glutaraldehyde cross-linked heart valves. 146,147 Since some surfactants such as sodium dodecyl sulfate reduce mineralization, these are used in commercial products, such as commercial porcine valves. 148,149 To prevent calcification induced by glutaraldehyde, chemical modification of the device surface has been investigated [e.g., using hyaluronic acid, 152 sulfonated poly(ethylene oxide) and heparin, 151,152 protamine, 153,154 bovine pericardium, [155][156][157] and l-arginine 156,157 ].…”
Section: Calcification Of Implantable Devicesmentioning
confidence: 99%
“…For instance, ethanol preincubation is known to be effective in preventing the calcification of glutaraldehyde cross-linked heart valves. 146,147 Since some surfactants such as sodium dodecyl sulfate reduce mineralization, these are used in commercial products, such as commercial porcine valves. 148,149 To prevent calcification induced by glutaraldehyde, chemical modification of the device surface has been investigated [e.g., using hyaluronic acid, 152 sulfonated poly(ethylene oxide) and heparin, 151,152 protamine, 153,154 bovine pericardium, [155][156][157] and l-arginine 156,157 ].…”
Section: Calcification Of Implantable Devicesmentioning
confidence: 99%
“…Early results are promising but require further investigation on larger studies. Alcohol solutions, including ethanol, have been investigated as a treatment to remove tissue phospholipids, thus preventing calcification (Pathak et al, 2004;Vyavahare et al, 1998). Besides, other techniques have been proposed to minimize the side effects of glutaraldehyde residues on GA-treated pericardium.…”
Section: Pericardium Anti-calcification Treatmentsmentioning
confidence: 99%
“…27,28,30,45 Calcification can also occur near the area with large leaflet flexion where both tensile and compressive planar stresses are induced. 30,46 It was also reported that large deflection induced substantial bending stresses in BHV leaflets during the cardiac cycle contributing significantly to the total resultant stresses. 14 Therefore, it is important to perform an accurate dynamic analysis on BHV and determine the regions of extreme stress concentration during the entire cardiac cycle.…”
Section: Introductionmentioning
confidence: 97%
“…In general, it has been widely accepted that structural degeneration is frequently accompanied by excessive calcification on BHV leaflets causing stenosis and cuspal tears even though the detailed mechanism of calcification is still not clearly understood. 1,30,41,46 Cuspal commissures and basal attachments are the common locations of the deposition of calcified substances on BHV. 27,28,30,45 Calcification can also occur near the area with large leaflet flexion where both tensile and compressive planar stresses are induced.…”
Section: Introductionmentioning
confidence: 99%